Various Tamponade in Surgery for Retinal Detachment Associated with Proliferative Vitreoretinopathy - Faraby Martha; Andi A Victor; Elvioza Elvioza; Ari Djatikusumo; Gitalisa A Andayani; Anggun R Yudantha (Majalah Oftalmologi Indonesia, 2015)
Background: To review the literature and report relative efficacy and safety of various tamponade agents used with surgery for rhegmatogenous retinal detachment (RRD) complicated by proliferative vitreoretinopathy (PVR) regarding functional success rate, anatomical success rate, and adverse effects. Methods: We searched articles from PubMed and Clinical Key database starting from the year of 1990 to November 2014. Information needed from all articles were extracted into data extraction sheet. We reviewed the efficacy of both tamponade agents regarding the postoperative visual acuity, macular attachment, and adverse effect. Results: Eight articles were included after fulfilling inclusion and exclusion criteria. Our analysis showed all studies shows an increasing visual acuity and percentage of macular attachment postoperatively of all type tamponade agents. Functional and anatomical success rate of Sulfur hexafluoride gas (SF6) was high in study with PVR stage B or less (94-98%). In patient with complex or recurrent RD associated with PVR, silicone oil had a better functional success (51% vs 32.5%) and better anatomical success (80% vs 60%) than SF6 gas. The anatomical success rate also higher in C3F8 than in SF6 group (73.9% vs 57.5% respectively). Functional and anatomical success rate of HSO as tamponade was high in patients with a severe PVR located mainly in the inferior quadrants (92.3%).Conclusion: As tamponade agents, C3F8 and silicone oil appear to have more visual and anatomic advantages over SF6 in participants with complex or recurrent RD associated with PVR. Silicone oil was better than C3F8 gas to obtain final visual and anatomic successs in patient with recurrent RD associated with higher grade PVR. Heavy silicone oil would be useful in particular cases complicated by recurrent inferior RD with PVR. Retinal redetachment, glaucoma, cataract, hypotony and keratopathy were reported in both gases and silicone group. Keywords: Tamponade in retinal detachment surgery, SF6, C3F8, silicon oil, and heavy silicone oil